MXene-based TiO2 / V-doped NiO multi-interface heterojunction, and preparation method and application thereof

CN123008922APending Publication Date: 2026-10-30JIANGXI NORMAL UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202610940806.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-06-27
Publication Date
2026-10-30

AI Technical Summary

Technical Problem

然而,现有的关于MXene/金属氧化物半导体异质结气敏材料的报道中采用的MXene基底多为多层手风琴状结构,并且MXene基底与金属氧化物纳米晶主要是以不均匀的混合物形式存在

Benefits of technology

[0019]本发明通过LiF辅助低温蚀刻结合超声剥离技术在较为温和的条件下获得了高产率、大横向尺寸的二维薄层Ti3C2Tx MXene纳米片,通过水浴法在其表面包覆均匀的Ni-VLDH纳米片,获得MXene/Ni-V LDH异质结,最后采用原位氧化技术直接将其氧化为MXene基TiO2/V掺杂NiO多界面异质结。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN123008922A_ABST
    Figure CN123008922A_ABST
Patent Text Reader

Abstract

The application belongs to the technical field of new materials and gas sensing, and particularly relates to a MXene-based TiO2 / V-doped NiO multi-interface heterojunction as well as a preparation method and application thereof. The MXene-based TiO2 / V-doped NiO multi-interface heterojunction comprises a substrate, a transition layer and a surface layer; the substrate is a two-dimensional MXene nanosheet, the transition layer is a TiO2 nanoparticle; the surface layer is a V-NiO nanosheet; a metal-semiconductor interface is formed between the two-dimensional MXene nanosheet and the TiO2 nanoparticle; and a semiconductor heterojunction interface is formed between the TiO2 nanoparticle and the V-NiO nanosheet. The preparation method is simple and efficient, the MXene-based TiO2 / V-doped NiO multi-interface heterojunction exhibits excellent selectivity in the detection of n-propanol, has high response value, low detection limit, and also performs excellently in long-term stability and humidity interference resistance, and can be used for effective detection of n-propanol in an actual environment.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This application belongs to the field of new materials and gas sensing technology, specifically relating to an MXene-based TiO2 / V-doped NiO multi-interface heterojunction, its preparation method, and its application. Background Technology

[0002] Volatile organic compounds (VOCs) are widely present in industrial production, environmental pollution, and human metabolism. n-propanol, a typical VOC gas, is widely used in solvents, coatings, and pharmaceuticals, and is commonly found in detergents, preservatives, and cosmetics. However, n-propanol is a toxic and volatile organic compound. Long-term exposure to n-propanol can adversely affect the human nervous and respiratory systems, and in severe cases, may lead to fainting or even death. These characteristics make n-propanol an important detection target in environmental monitoring and industrial safety. Therefore, developing high-performance n-propanol gas sensors has significant scientific and practical value. Metal oxide semiconductor (MOS) gas sensors have attracted considerable attention. Currently, MOS has become the mainstream system for semiconductor gas sensor material research due to its low cost and simple fabrication. However, traditional MOS materials have several limitations.

[0003] In the design of gas-sensitive materials, most single metal oxide semiconductors have low conductivity and limited carrier transport paths, making it difficult to efficiently amplify the material resistance changes caused by gas adsorption. Furthermore, single materials lack abundant interfaces, making it difficult to simultaneously optimize gas adsorption, electron transport, and reactive oxygen species regulation. Therefore, constructing multi-component heterojunction gas-sensitive materials has become an effective way to regulate gas-sensing performance. Heterojunctions can not only form built-in electric fields to promote carrier separation and transport, but also regulate the local electronic structure through interfacial coupling effects, thereby enhancing the interaction between gas molecules and reactive oxygen species. Notably, in recent years, constructing heterojunctions by combining metal oxide semiconductor nanocrystals with transition metal carbide / nitride (MXene) materials, which possess excellent conductivity and surface activity, has become an important strategy for improving gas-sensing performance. However, existing reports on MXene / metal oxide semiconductor heterojunction gas-sensitive materials often use multilayer accordion-like MXene substrates, and the MXene substrate and metal oxide nanocrystals mainly exist in a non-uniform mixture. This not only makes it difficult to fully utilize the high specific surface area and high activity of MXene, but also makes it difficult to form rich and stable interfacial contacts between the semiconductor nanocrystals and the MXene substrate, thus hindering the full utilization of surface active sites and efficient transport of interfacial charges. In conclusion, there is an urgent need to develop two-dimensional MXene / metal oxide semiconductor heterojunction gas-sensitive materials with rich and stable heterojunction interfaces. Summary of the Invention

[0004] The purpose of this invention is to at least solve one of the technical problems existing in the prior art, and to provide an MXene-based TiO2 / V doped NiO multi-interface heterojunction, its preparation method and application.

[0005] The technical solution of the present invention is as follows: In a first aspect, the present invention provides an MXene-based TiO2 / V-doped NiO multi-interface heterojunction, wherein the MXene-based TiO2 / V-doped NiO multi-interface heterojunction includes a substrate and a transition layer and a surface layer sequentially disposed on the substrate; The substrate is a two-dimensional MXene nanosheet, the transition layer is TiO2 nanoparticles, and the surface layer is a V-doped NiO nanosheet (V-NiO nanosheet for short). A metal-semiconductor interface is formed between the two-dimensional MXene nanosheets and the TiO2 nanoparticles; a semiconductor heterostructure interface is formed between the TiO2 nanoparticles and the V-NiO nanosheets.

[0006] TiO2, as a typical n-type semiconductor, facilitates the formation of heterojunctions and the modulation of band structure. By doping NiO with V, the oxygen vacancy content and local electronic structure of the material are modulated, thereby enhancing its reactivity during the n-propanol oxidation process. Therefore, this invention utilizes a multi-component heterojunction constructed from MXene, TiO2, and V-doped NiO to effectively promote carrier migration and interfacial reactions. Simultaneously, V-doping-induced defect modulation enhances the material's reactivity in the gas-sensitive reaction process, thus synergistically improving the gas-sensing performance of MXene / TiO2 / V-NiO for n-propanol. Furthermore, the MXene-based TiO2 / V-doped NiO multi-interface heterojunction not only possesses a large gas adsorption and reaction surface area but also enhances the stability of the original MXene, providing important insights into the multi-interface charge transport mechanism in resistive gas sensors and offering a novel material system for n-propanol detection.

[0007] As a further preferred embodiment, the loading of V-NiO nanosheets in the MXene-based TiO2 / V-doped NiO multi-interface heterojunction is 70~85 wt%, and the V doping amount is 4~7 wt%.

[0008] As a further preferred embodiment, the specific surface area of ​​the MXene-based TiO2 / V-doped NiO multi-interface heterojunction is 80 m². 2 / g~100 m 2 / g; The MXene nanosheets have a lateral dimension of 4 μm to 11 μm, the TiO2 nanoparticles have a size of 4 nm to 10 nm, and the V-NiO nanosheets have a thickness of 30 nm to 60 nm.

[0009] As a further preferred embodiment, the substrate is a two-dimensional Ti3C2T synthesized by low-temperature etching and ultrasonic ablation. x MXene nanosheets. The MXene used in this invention to construct heterojunction substrates differs from traditional accordion-shaped multilayer MXene. This structure can fully utilize its large specific surface area, enabling TiO2 nanoparticles and V-doped NiO nanosheets to form sufficient contact interfaces with the MXene substrate, providing excellent electron transport channels and more reactive sites.

[0010] Secondly, the present invention provides a method for preparing the above-mentioned MXene-based TiO2 / V-doped NiO multi-interface heterojunction, comprising the following steps: S1. Preparation of two-dimensional MXene nanosheets; S2. Ni-V double hydroxide (Ni-VLDH) nanosheets are grown in situ on the surface of the two-dimensional MXene nanosheets by water bath method to obtain the transition product MXene / Ni-V LDH heterojunction; S3. The transition product MXene / Ni-V LDH heterojunction is calcined to oxidize the MXene portion in situ to generate TiO2 nanoparticles, and Ni-V LDH is converted into V-doped NiO nanosheets to obtain the MXene-based TiO2 / V-doped NiO multi-interface heterojunction.

[0011] As a further preferred embodiment, in S1, the two-dimensional MXene nanosheets are obtained by water bath method combined with ultrasonic exfoliation of accordion-shaped MXene; More preferably, in S1, the specific preparation method of the two-dimensional MXene nanosheets includes the following steps: Lithium fluoride was dissolved in concentrated hydrochloric acid and stirred to obtain a reaction solution; Aluminum carbide was added to the reaction solution for a water bath reaction. After the reaction, the solution was washed with dilute hydrochloric acid and deionized water in sequence, and then centrifuged. The solution was then subjected to ultrasonic exfoliation and reaction under an inert gas atmosphere. After the reaction, the solution was centrifuged, the supernatant was taken, frozen, and dried to obtain the two-dimensional MXene nanosheets.

[0012] The MXene used in this invention to construct heterojunction substrates differs from traditional accordion-shaped multilayer MXenes. This structure can fully utilize its large specific surface area, enabling TiO2 nanoparticles and V-doped NiO nanosheets to form sufficient contact interfaces with the MXene substrate, providing excellent electron transport channels and more reactive sites.

[0013] As a further preferred embodiment, the molar ratio of lithium fluoride to aluminum carbide is 3.5~15:1, more preferably 10~12:1; The concentration of the concentrated hydrochloric acid is 10 mol / L to 12 mol / L, and the concentration of the dilute hydrochloric acid is 0.5 to 1.5 mol / L. The ultrasonic power during ultrasonic ablation is 50~70 W.

[0014] As a further preferred embodiment, the inert gas is argon.

[0015] In the above reaction process, lithium fluoride reacts with concentrated hydrochloric acid to generate hydrofluoric acid, and the change in hydrofluoric acid concentration has a significant impact on the etching effect of the aluminum layer in aluminum carbide. When the hydrofluoric acid concentration is too low, the aluminum layer cannot be effectively removed, making it difficult to obtain an MXene colloidal solution; conversely, if the hydrofluoric acid concentration is too high, it will lead to a decrease in the specific surface area of ​​the obtained MXene sheets and a large number of sheet breakage phenomena. Considering both etching efficiency and sheet integrity, the optimal amount of lithium fluoride is 3 g, and the optimal amount of concentrated hydrochloric acid is 40 mL. This condition can ensure that the aluminum layer is completely etched while maintaining the integrity of the MXene sheet structure to the greatest extent.

[0016] As a further preferred embodiment, in S2, the specific preparation method for obtaining the transition product MXene / Ni-V LDH heterojunction by in-situ growth of Ni-V LDH nanosheets on the surface of the two-dimensional MXene nanosheets using a water bath method includes the following steps: Ni(NO3)2·6H2O, VCl3, and CO(NH2)2 were dissolved in deionized water and stirred. During the stirring process, the two-dimensional MXene nanosheets were added to obtain the reaction solution. The reaction solution was placed in a reaction vessel and then heated to carry out the reaction at a temperature of 100-120 °C for 10-12 h. After the reaction was completed, the mixture was washed and dried to obtain the transition product MXene / Ni-V LDH heterojunction.

[0017] As a further preferred embodiment, in S2, the molar ratio of Ni(NO3)2·6H2O, VCl3, and CO(NH2)2 is 13~14:0.8~3:0.0055~0.0065, more preferably 13.4:1:0.006.

[0018] As a further preferred embodiment, in S3, the specific preparation method for growing TiO2 nanoparticles and V-NiO nanosheets on the surface of the transition product MXene / Ni-V LDH heterojunction by high-temperature calcination to obtain the MXene-based TiO2 / V-doped NiO multi-interface heterojunction includes the following steps: The transition product MXene / Ni-V LDH heterojunction was placed in a quartz boat and spread out evenly. The quartz boat was placed in a muffle furnace and calcined at a high temperature of 300~350 ℃ for 1~3 h to obtain the MXene-based TiO2 / V-doped NiO multi-interface heterojunction.

[0019] This invention obtains high-yield, large-lateral-size two-dimensional thin-layer Ti3C2Tx MXene nanosheets under relatively mild conditions by combining LiF-assisted low-temperature etching with ultrasonic exfoliation. Uniform Ni-VLDH nanosheets are then coated onto the surface of the nanosheets using a water bath method to obtain an MXene / Ni-V LDH heterojunction. Finally, in-situ oxidation is used to directly oxidize the nanosheets into an MXene-based TiO2 / V-doped NiO multi-interface heterojunction.

[0020] This invention investigates the gas-sensing properties of this heterojunction structure for some typical harmful environmental gases, especially VOCs. Through the design of an efficient multi-interface electron transport channel, the charge signal generated during the gas-sensing reaction is efficiently converted into a resistance signal, thereby comprehensively improving the gas-sensing performance of the MXene-based TiO2 / V-doped NiO multi-interface heterojunction for the typical VOC gas n-propanol. Based on the above results, using a combination of various spectroscopic techniques (including in-situ red surface characterization) and density functional theory-based calculations, key issues such as the adsorption of target gas molecules, changes in the electronic structure of the surface and interface during the gas-sensing process, and real-time changes in charge transfer, surface species, and adsorbed groups with the ambient atmosphere were studied in depth, elucidating the gas-sensing mechanism. This invention will not only greatly expand the application of MXene materials in the field of resistive gas sensors, but also provide important guidance for understanding the working mechanism of resistive gas sensors.

[0021] Thirdly, the present invention provides a gas sensor comprising the aforementioned MXene-based TiO2 / V-doped NiO multi-interface heterojunction as a gas-sensitive material.

[0022] This invention constructs a semiconductor gas sensor by drop-coating a gas-sensitive material onto a gas-sensitive substrate, wherein the gas-sensitive substrate is an Al2O3 gas-sensitive substrate.

[0023] The aforementioned Al2O3 gas-sensitive substrate is a commercially available flat-plate Al2O3 gas-sensitive substrate. This substrate is composed of inexpensive and readily available Al2O3, and its surface simultaneously features a pair of heating Pt interdigitated electrodes and a pair of resistance signal collection electrodes. Substrate heating and resistance signal collection are very convenient, and the two pairs of electrodes do not interfere with each other. An MXene-based TiO2 / V-doped NiO multi-interface heterojunction is used as the gas-sensitive sensing layer for surface gas adsorption and gas-sensitive reactions.

[0024] Fourthly, the present invention provides the application of the above-mentioned gas sensor in the detection of n-propanol gas.

[0025] This invention has at least one of the following beneficial effects: The MXene-based TiO2 / V-doped NiO multi-interface heterojunction provided by this invention possesses a large specific surface area, significantly increasing the gas adsorption activity on the material surface and enhancing the stability of the original MXene. This provides important insights into the study of multi-interface charge transport mechanisms in resistive gas sensors, offering structural advantages over traditional accordion-shaped multilayer MXene nanosheets. Furthermore, through the design of efficient multi-interface electron transport channels, the efficient conversion of charge signals generated during the gas-sensitive reaction into resistance signals is achieved, thereby comprehensively improving the gas-sensing performance of the MXene-based TiO2 / V-doped NiO multi-interface heterojunction for the typical VOC gas n-propanol. At the preferred operating temperature, the MXene-based TiO2 / V-doped NiO multi-interface heterojunction exhibits excellent gas selectivity for n-propanol with high response values, low detection limits, and high sensitivity. This invention demonstrates excellent long-term stability and resistance to humidity interference, showing broad application prospects in practical production. Attached Figure Description

[0026] Figure 1 The diagram shows (a) a schematic diagram of the synthesis process of MXene / TiO2 / V-NiO; (bc) SEM images of MXene nanosheets prepared in Comparative Example 1; (de) SEM images of MXene / TiO2 prepared in Comparative Example 2; (fg) SEM images of MXene / TiO2 / V-NiO prepared in Example 3; (hk) HRTEM images of MXene / TiO2 / V-NiO prepared in Example 3; and (lq) energy dispersive spectroscopy (EDS) elemental distribution of MXene / TiO2 / V-NiO prepared in Example 3.

[0027] Figure 2The following are nitrogen adsorption-desorption isotherms and pore size distribution curves for different samples: (a) MXene / TiO2 / V-NiO prepared in Example 3; (b) MXene / TiO2 / NiO prepared in Comparative Example 4; (c) V-NiO prepared in Comparative Example 3; (d) MXene / TiO2 prepared in Comparative Example 2; and (e) MXene prepared in Comparative Example 1.

[0028] Figure 3 The following are XRD patterns of various samples prepared in Example 3 and Comparative Examples 1-4: (a) XRD patterns of various samples prepared in Example 3 and Comparative Examples 1-4; (b) Schematic diagrams of the atomic structures of MXene / TiO2 / V-NiO prepared in Example 3, MXene / TiO2 / NiO prepared in Comparative Example 4, V-NiO prepared in Comparative Example 3, MXene / TiO2 prepared in Comparative Example 2, and MXene prepared in Comparative Example 1 (from left to right); (ce) and (gh) are XPS spectra of C 1s, Ti 2p, O 1s, Ni 2p, and V 2p, respectively; (f) EPR spectra of MXene / TiO2 / V-NiO prepared in Example 3 and MXene / TiO2 / NiO prepared in Comparative Example 4.

[0029] Figure 4 (ab) shows the response values ​​of different samples prepared in Example 3 and Comparative Examples 1-4 to 100 ppm n-propanol at different temperatures, and the amplified response values ​​of some samples; (cg) shows the repeatability of the response of different samples prepared in Example 3 and Comparative Examples 2-4 to 100 ppm n-propanol at 350 °C; (h) shows the response and recovery time of MXene / TiO2 / V-NiO prepared in Example 3 to 100 ppm n-propanol at 350 °C; (i) shows the response values ​​of MXene / TiO2 / V-NiO prepared in Example 3 to different types of gases.

[0030] Figure 5 The following figures show (ae) the dynamic response characteristics of different samples prepared in Example 3 and Comparative Examples 1-4 to n-propanol at 350 °C with concentrations ranging from 1 ppm to 2000 ppm; (f) the detection limit of MXene / TiO2 / V-NiO prepared in Example 3 to n-propanol. Figure 6 (a) shows the long-term stability of the MXene / TiO2 / V-NiO sensor prepared in Example 3 against 100 ppm n-propanol and the change in baseline resistance; Figure 6 (b) shows the response value and baseline resistance of the MXene / TiO2 / V-NiO sensor prepared in Example 3 to 100 ppm n-propanol at different humidity levels.

[0031] Figure 7The images show the UV surface photoelectron spectra (UPS), Kubelka-Munk transform reflectance spectra, and Mott-Schottky curves derived from the UV-Vis absorption spectra of different samples; (a), (b), and (c) are the UPS, Kubelka-Munk transform reflectance spectra, and Mott-Schottky curves of V-NiO prepared in Comparative Example 3, respectively; (d), (e), and (f) are the UPS, Kubelka-Munk transform reflectance spectra, and Mott-Schottky curves of MXene / TiO2 prepared in Comparative Example 2, respectively.

[0032] Figure 8 The image shows the in-situ Fourier transform red surface spectrum of the MXene-based TiO2 / V-doped NiO multi-interface heterostructure prepared in Example 3 in a n-propanol atmosphere; where (a) is the total in-situ Fourier transform red surface spectrum; and (b) is the spectrum at 2500-4000 cm⁻¹. -1 (c) In-situ Fourier transform red surface spectra within the range of 600–2000 cm⁻¹; -1 In-situ Fourier transform red surface spectra within the range; (d) shows the spectra in the 2000–2800 cm⁻¹ range. -1 In-situ Fourier transform red surface spectra within the range. Detailed Implementation

[0033] To make the technical problems solved, the technical solutions, and the beneficial effects of this invention clearer, the invention will be further described in detail below with reference to the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are merely illustrative of the invention and are not intended to limit the invention.

[0034] The following embodiments of the present invention provide an MXene-based TiO2 / V-doped NiO multi-interface heterostructure, the preparation process of which is as follows: Figure 1 As shown in (a), firstly, the Al layer in Ti3AlC2 is removed by a low-temperature water bath etching method using LiF / HCl to generate hydrofluoric acid in situ. Then, accordion-shaped MXene is ultrasonically exfoliated to obtain two-dimensional MXene nanosheets. Next, Ni-V LDH nanosheets are grown in situ on the surface of the two-dimensional MXene nanosheets by a water bath method to obtain a transition product MXene / Ni-V LDH heterojunction. Finally, the MXene portion in the transition product MXene / Ni-V LDH is oxidized in situ to generate TiO2 nanoparticles by high-temperature calcination in a muffle furnace, and the Ni-V LDH is converted into V-doped NiO nanosheets to obtain the MXene-based TiO2 / V-doped NiO multi-interface heterojunction.

[0035] This invention constructs a TiO2 / V-NiO ternary heterojunction gas-sensitive material with two-dimensional MXene nanosheets as a substrate for the detection of n-propanol gas. The MXene used to construct the heterojunction substrate differs from traditional accordion-shaped multilayer MXene. This substrate is a two-dimensional Ti3C2T synthesized by low-temperature etching and ultrasonic exfoliation. x MXene nanosheets. This structure fully utilizes the large specific surface area of ​​MXene, enabling TiO2 nanoparticles and V-doped NiO nanosheets to form sufficient contact interfaces with the MXene substrate, providing excellent electron transport channels and more reactive sites. Subsequently, two-dimensional Ni-V LDH nanosheets are deposited on MXene using a water bath method, followed by high-temperature oxidation to directly obtain an MXene-based TiO2 / V-doped NiO multi-interface heterojunction material. TiO2, as a typical n-type semiconductor, facilitates the formation of heterointerfaces and modulates the band structure. Furthermore, V-doping NiO modulates the oxygen vacancy content and local electronic structure, thereby improving the material's reactivity during the n-propanol oxidation process. The multi-component heterointerface constructed between MXene, TiO2, and V-doped NiO effectively promotes carrier migration and interfacial reactions, while V-doping-induced defect modulation enhances the material's reactivity in gas-sensitive reactions, thus synergistically improving the gas-sensing performance of MXene / TiO2 / V-NiO for n-propanol. Furthermore, the MXene-based TiO2 / V-doped NiO multi-interface heterojunction not only has a large specific surface area for gas adsorption and reaction, but also enhances the stability of the original MXene, providing important insights into the study of multi-interface charge transport mechanisms in resistive gas sensors, and also providing a new material system for the detection of n-propanol.

[0036] The present invention will be further described in detail below with reference to specific embodiments, but the present invention is not limited to the following specific embodiments.

[0037] Example 1 A method for preparing an MXene-based TiO2 / V-doped NiO multi-interface heterojunction includes the following steps: (1) 1 g of lithium fluoride (LiF) and 40 mL of concentrated hydrochloric acid (HCl, concentration 11.6 mol / L) were added to a polytetrafluoroethylene autoclave, and the mixture was continuously stirred magnetically for 0.5 h to obtain a reaction solution. 2 g of aluminum carbide (Ti3AlC2MAX) was slowly added to the reaction solution in small amounts several times, with the time controlled at 15 min. Finally, the reaction solution was kept at a constant temperature in a water bath, with the reaction temperature set at 35 ℃ and the reaction time set at 24 h. After the reaction was completed, the mixture was washed with dilute hydrochloric acid (HCl, concentration 1 mol / L) and centrifuged. Then it was washed with deionized water and centrifuged until the pH value was about 7. Then it was sonicated under an argon atmosphere for 2 h at a power setting of 60 W. Finally, it was centrifuged for 60 min, and the upper dark green Ti3C2MAX layer was collected. X MXene colloids were freeze-dried to obtain MXene nanosheets.

[0038] (2) Weigh Ni(NO3)2·6H2O and VCl3 according to a molar ratio of 13.4:3, dissolve them in deionized water with 0.36 g CO(NH2)2 and stir. During the stirring process, add MXene nanosheets accounting for 30% of the total mass of the reactants to obtain a reaction solution. Place the reaction solution in a reaction vessel and then heat it to carry out the reaction at a reaction temperature of 100 °C for 12 h. After the reaction is completed, wash and dry to obtain the transition product MXene / Ni-V LDH heterojunction.

[0039] (3) The transition product MXene / Ni-V LDH heterojunction is placed in a quartz boat and spread evenly; the quartz boat is placed in a muffle furnace for high-temperature calcination at a reaction temperature of 300 °C and a reaction time of 2 h to obtain the MXene-based TiO2 / V doped NiO multi-interface heterojunction.

[0040] Example 2 A multi-interface heterojunction based on MXene TiO2 / V doped NiO is prepared by the following steps: (1) 2 g of lithium fluoride (LiF) and 40 mL of concentrated hydrochloric acid (HCl, concentration 11.9 mol / L) were added to a polytetrafluoroethylene autoclave, and the mixture was continuously stirred magnetically for 0.5 h to obtain a reaction solution. 2 g of aluminum carbide (Ti3AlC2MAX) was slowly added to the reaction solution in small amounts several times, with the time controlled at 15 min. Finally, the reaction solution was kept at a constant temperature in a water bath, with the reaction temperature set at 35 ℃ and the reaction time set at 24 h. After the reaction was completed, the mixture was washed with dilute hydrochloric acid (HCl, concentration 1 mol / L) and centrifuged. Then it was washed with deionized water and centrifuged until the pH value was about 7. Then it was sonicated under an argon atmosphere for 2 h at a power setting of 60 W. Finally, it was centrifuged for 60 min, and the upper dark green Ti3C2MAX layer was collected. XMXene colloids were freeze-dried to obtain MXene nanosheets.

[0041] (2) Weigh Ni(NO3)2·6H2O and VCl3 according to a molar ratio of 13.4:2, dissolve them in deionized water with 0.36 g CO(NH2)2 and stir. During the stirring process, add MXene nanosheets accounting for 25% of the total mass of the reactants to obtain a reaction solution. Place the reaction solution in a reaction vessel and then heat it to carry out the reaction at a reaction temperature of 110 °C for 11 h. After the reaction is completed, wash and dry to obtain the transition product MXene / Ni-V LDH heterojunction.

[0042] (3) The transition product MXene / Ni-V LDH heterojunction is placed in a quartz boat and spread evenly; the quartz boat is placed in a muffle furnace for high-temperature calcination at a reaction temperature of 350 °C and a reaction time of 2 h to obtain the MXene-based TiO2 / V doped NiO multi-interface heterojunction.

[0043] Example 3 A multi-interface heterojunction based on MXene TiO2 / V doped NiO is prepared by the following steps: (1) 3 g of lithium fluoride (LiF) and 40 mL of concentrated hydrochloric acid (HCl, concentration 12.4 mol / L) were added to a polytetrafluoroethylene autoclave, and the mixture was continuously stirred magnetically for 0.5 h to obtain a reaction solution. 2 g of aluminum carbide (Ti3AlC2MAX) was slowly added to the reaction solution in small amounts several times, with the time controlled at 15 min. Finally, the reaction solution was kept at a constant temperature in a water bath, with the reaction temperature set at 35 ℃ and the reaction time set at 24 h. After the reaction was completed, the mixture was washed with dilute hydrochloric acid (HCl, concentration 1 mol / L) and centrifuged. Then it was washed with deionized water and centrifuged until the pH value was about 7. Then it was sonicated under an argon atmosphere for 2 h with a power set at 60 W. Finally, it was centrifuged for 60 min, and the upper dark green Ti3C2MAX layer was collected. X MXene colloids were freeze-dried to obtain MXene nanosheets.

[0044] (2) Weigh Ni(NO3)2·6H2O and VCl3 at a molar ratio of 13.4:1, dissolve them in deionized water with 0.36 g CO(NH2)2 and stir. During stirring, add MXene nanosheets accounting for 20% of the total mass of the reactants to obtain a reaction solution. Place the reaction solution in a reaction vessel and heat it to carry out the reaction at a reaction temperature of 120 °C for 10 h. After the reaction is completed, wash and dry to obtain the transition product MXene / Ni-V LDH heterojunction.

[0045] (3) The transition product MXene / Ni-V LDH heterojunction is placed in a quartz boat and spread evenly; the quartz boat is placed in a muffle furnace for high-temperature calcination at a reaction temperature of 350 °C and a reaction time of 2 h to obtain the MXene-based TiO2 / V doped NiO multi-interface heterojunction.

[0046] Example 4 A multi-interface heterojunction based on MXene TiO2 / V doped NiO is prepared by the following steps: (1) 4 g of lithium fluoride (LiF) and 40 mL of concentrated hydrochloric acid (HCl, concentration 12.4 mol / L) were added to a polytetrafluoroethylene autoclave, and the mixture was continuously stirred magnetically for 0.5 h to obtain a reaction solution. 2 g of aluminum carbide (Ti3AlC2MAX) was slowly added to the reaction solution in small amounts several times, with the time controlled at 15 min. Finally, the reaction solution was kept at a constant temperature in a water bath, with the reaction temperature set at 35 ℃ and the reaction time set at 24 h. After the reaction was completed, the mixture was washed with dilute hydrochloric acid (HCl, concentration 1 mol / L) and centrifuged. Then it was washed with deionized water and centrifuged until the pH value was about 7. Then it was sonicated under an argon atmosphere for 2 h with a power set at 60 W. Finally, it was centrifuged for 60 min, and the upper dark green Ti3C2MAX layer was collected. X MXene colloids were freeze-dried to obtain MXene nanosheets.

[0047] (2) Weigh Ni(NO3)2·6H2O and VCl3 in a molar ratio of 13.4:0.8, dissolve them in deionized water with 0.36 g CO(NH2)2 and stir. During stirring, add MXene nanosheets accounting for 15% of the total mass of the reactants to obtain a reaction solution. Place the reaction solution in a reaction vessel and heat it to carry out the reaction at a reaction temperature of 120 °C for 10 h. After the reaction is completed, wash and dry to obtain the transition product MXene / Ni-V LDH heterojunction.

[0048] (3) The transition product MXene / Ni-V LDH heterojunction is placed in a quartz boat and spread evenly; the quartz boat is placed in a muffle furnace for high-temperature calcination at a reaction temperature of 350 °C and a reaction time of 2 h to obtain the MXene-based TiO2 / V doped NiO multi-interface heterojunction.

[0049] Comparative Example 1 An MXene nanosheet was prepared using the same method as step (1) in Example 3, and the preparation method specifically included the following steps: 3 g of lithium fluoride (LiF) and 40 mL of concentrated hydrochloric acid (HCl, 12.4 mol / L) were added to a polytetrafluoroethylene autoclave, and the mixture was continuously stirred magnetically for 0.5 h to obtain a reaction solution. 2 g of aluminum carbide (Ti3AlC2MAX) was slowly added to the reaction solution in small batches over 15 min periods. The reaction solution was then kept at a constant temperature of 35 °C for 24 h in a water bath. After the reaction, the mixture was washed with dilute hydrochloric acid (HCl, 1 mol / L) and centrifuged. It was then washed with deionized water and centrifuged until the pH value was approximately 7. The mixture was then sonicated under an argon atmosphere for 2 h at a power of 60 W, and finally centrifuged for 60 min. The upper dark green Ti3C2MAX layer was collected. X MXene colloids were freeze-dried to obtain MXene nanosheets.

[0050] Comparative Example 2 An MXene / TiO2 nanoparticle heterostructure is prepared by the following steps: Weigh 50 mg of MXene nanosheets (prepared in Comparative Example 1), place them in a quartz boat and spread them out. Then place the quartz boat in a muffle furnace and calcine it at a high temperature of 350 °C for 2 h to obtain MXene / TiO2 nanoparticle heterojunction.

[0051] Comparative Example 3 A V-NiO powder, the preparation method of which includes the following steps: Ni(NO3)2·6H2O and VCl3 were dissolved in deionized water at a molar ratio of 13.4:1. 0.36 g of CO(NH2)2 was added and mixed thoroughly, and the mixture was stirred for 0.5 h to obtain a reaction solution. The reaction solution was placed in a reaction vessel and heated to 120 °C for 10 h. After the reaction, the obtained product was washed alternately with deionized water and ethanol, and dried to obtain green Ni-V LDH powder. The green powder was placed in a quartz boat and calcined in a muffle furnace at 350 °C for 2 h to obtain V-NiO powder.

[0052] Comparative Example 4 An MXene / TiO2 / NiO heterojunction is prepared by the following steps: Ni(NO3)2·6H2O was dissolved in deionized water, and 0.36 g of CO(NH2)2 was added and stirred. During stirring, MXene nanosheets (prepared in Comparative Example 1) were added, with the MXene nanosheets accounting for 20% of the total mass of the reactants, to obtain a reaction solution. The reaction solution was placed in a reaction vessel and heated to 120 °C for 10 h. After the reaction, the obtained product was washed alternately with deionized water and ethanol, and dried to obtain MXene / Ni-LDH powder. The powder was placed in a quartz boat and calcined in a muffle furnace at 350 °C for 2 h to obtain an MXene / TiO2 / NiO heterojunction.

[0053] Example 5 The materials obtained in Example 3 and Comparative Examples 1-4 were characterized and their performance tested. The specific results are as follows: (1) The morphology of the prepared material was characterized by SEM and TEM.

[0054] Figure 1 (bc) shows ultrathin two-dimensional MXene nanosheets. These large-area sheets can provide more active adsorption sites, which are very important for subsequent material surface deposition and gas sensing reactions. Figure 1 (de) shows that TiO2 particles are uniformly loaded on the surface of MXene nanosheets, which is beneficial for enhancing the interfacial contact between V-NiO and the MXene / TiO2 substrate, playing a role in interfacial bridging and charge transport regulation during gas sensing. Figure 1 (fg) shows the morphology of the MXene-based TiO2 / V-doped NiO multi-interface heterostructure. The sheet-like V-NiO is uniformly deposited on the MXene / TiO2 surface, which effectively alleviates the aggregation of V-NiO nanosheets, which is conducive to building a more open heterostructure and a fast gas diffusion channel, thereby improving the utilization efficiency of the target gas and the surface reaction efficiency. Figure 1 Image (hk) is obtained by further studying the microstructure of the sample using high-resolution transmission electron microscopy (HRTEM). Clear heterostructures between MXene, TiO2, and V-NiO can be observed, providing the structural basis for interfacial electronic coupling and charge transport. The observed lattice spacings on this surface are 0.244, 0.237, and 0.208 nm, corresponding to the (103) crystal plane of MXene, the (004) crystal plane of TiO2, and the (200) crystal plane of NiO, respectively. Figure 1(lq) is an elemental distribution map of the material analyzed using energy-dispersive spectroscopy (EDS), which shows that C, Ti, O, Ni, and V are uniformly distributed throughout the structure. These results clearly demonstrate that MXene nanosheets serve as an effective substrate for the uniform deposition of TiO2 nanoparticles and V-NiO nanosheets, thereby constructing an MXene-based TiO2 / V-doped NiO multi-interface heterostructure.

[0055] (2) In order to further analyze the microstructure of the sample, the specific surface area and pore size of the sample were determined by nitrogen adsorption-desorption isotherm test.

[0056] To determine the specific surface area and pore size of the samples, nitrogen adsorption-desorption isotherms were measured for MXene nanosheets, MXene / TiO2, V-NiO, MXene / TiO2 / NiO, and MXene / TiO2 / V-NiO. Figure 2 As shown, the nitrogen adsorption-desorption isotherms of MXene nanosheets, MXene / TiO2, V-NiO, MXene / TiO2 / NiO, and MXene / TiO2 / V-NiO all belong to type IV isotherms and have H3-type hysteresis loops, indicating the presence of mesoporous structures in the samples. Furthermore, based on the specific surface area and pore size parameters of all samples, MXene / TiO2 exhibits the largest specific surface area (199.4667 m²). 2 / g), this is because MXene (2.846m 2 The high-temperature calcination of MXene / TiO2 / V-NiO produced a large number of TiO2 particles, significantly increasing its specific surface area. Under the support of MXene / TiO2, the specific surface area of ​​MXene / TiO2 / V-NiO (91.7799 m² / g) was significantly increased. 2 The specific surface area of ​​V-NiO (16.5208 m² / g) is higher than that of V-NiO. 2 The specific surface area ( / g) was increased by approximately 5 times. These results indicate that MXene / TiO2 can not only serve as a two-dimensional support substrate for V-NiO nanosheets, but also significantly improve the specific surface area and pore structure of the composite material, thereby providing more adsorption sites for gas adsorption and surface reactions.

[0057] (3) The phase composition of the prepared sample was characterized by X-ray diffraction (XRD).

[0058] Figure 3Figures (ab) show the X-ray diffraction (XRD) characterization results of the prepared samples and the side view structures of each model, respectively. As shown in the figure, MXene exhibits obvious diffraction peaks at 2θ = 7.2°, 17.1°, 27.2°, 34.6°, 42.3°, and 61.0°, which is consistent with existing reports. After high-temperature calcination, new characteristic peaks appear at 2θ = 25.3°, 37.8°, 48.0°, 53.9°, and 55.1°, which are consistent with the anatase phase of TiO2 (JCPDS No. 21-1272). In the XRD patterns of MXene / TiO2 / V-NiO, MXene / TiO2 / NiO, and V-NiO, characteristic peaks appear at approximately 2θ = 37.2°, 43.2°, 62.9°, 75.4°, and 79.4°, which is consistent with the karnite phase of NiO (JCPDS No. 71-1179). For MXene / TiO2 / V-NiO and MXene / TiO2 / NiO, the samples still retain the relevant characteristic peaks of MXene / TiO2, but their diffraction intensity is weaker compared to the relevant peaks of V-NiO or NiO. This is due to the masking effect of the stronger diffraction signal of NiO in the composite system. In addition, EDS shows the presence of V element in MXene / TiO2 / V-NiO, but no characteristic peaks of vanadium oxide are observed in the XRD pattern. This may be because the low V content largely masks its diffraction peaks or some V species enter the NiO lattice and do not form an independent vanadium oxide phase. Compared with MXene / TiO2 / NiO, its diffraction peaks related to NiO show a certain degree of broadening, indicating that the introduction of V may have suppressed the growth of NiO grains. This phenomenon can be attributed to V doping-induced local lattice distortion and defect formation.

[0059] (4) In order to analyze the chemical state of the samples more thoroughly, X-ray photoelectron spectroscopy (XPS) was performed on MXene, MXene / TiO2, V-NiO, MXene / TiO2 / NiO and MXene / TiO2 / V-NiO.

[0060] Figure 3 (c) shows the high-resolution C 1s spectra of various materials, where the binding energies of MXene are 282.35 eV, 284.77 eV, 286.55 eV, and 288.92 eV, corresponding to C-Ti, CC, CO, and OC=O, respectively. After high-temperature calcination, the intensity of the C-Ti peak is significantly weakened because MXene is oxidized at high temperature to form TiO2 particles. Figure 3 (d) shows the high-resolution Ti 2p spectra of various materials. In MXene, Ti 2p... 3 / 2 and Ti 2p 1 / 2The peaks appear at 455.59 eV and 461.66 eV, and can be decomposed into four parts: Ti-C, Ti-F, Ti-O, and TiO2, located at 455.40 eV, 456.28 eV, 457.32 eV, and 458.71 eV, respectively. After high-temperature oxidation, most of the peak signals decrease significantly, while the TiO2 peak is significantly enhanced, because MXene is mainly occupied by TiO2. In the MXene / TiO2 / V-NiO ternary heterostructure, Ti 2p 3 / 2 and Ti 2p 1 / 2 The peaks appear at 458.31 eV and 464.18 eV, which is consistent with the Ti 2p of MXene / TiO2. 3 / 2 and Ti 2p 1 / 2 The peaks show a negative shift compared to the previous values. High-resolution O 1s spectra are as follows: Figure 3 As shown in (e), the peaks of MXene / TiO2 near the binding energies of 530.36 eV and 531.94 eV are attributed to Ti-O bonds and surface chemisorbed oxygen (O2), respectively. ads After the introduction of NiO, the O 1s spectrum of MXene / TiO2 / NiO undergoes significant changes and can be decomposed into lattice oxygen (O). L Oxygen vacancy-related oxygen (O) V ) and surface-adsorbed oxygen (O ads Compared to MXene / TiO2 / NiO, MXene / TiO2 / V-NiO exhibits significantly enhanced O2 content. V Related components, while electron paramagnetic resonance (EPR) spectrum ( Figure 3 (f) further confirms this result. MXene / TiO2 / V-NiO shows a significantly stronger EPR signal than MXene / TiO2 / NiO, indicating a higher concentration of oxygen vacancies. This result is consistent with O 1s XPS analysis, demonstrating that V doping can effectively perturb the coordination environment of local Ni-O and induce the formation of more oxygen vacancies. The resulting defect-rich surface can modulate the electronic structure and coordination stability of adjacent lattice oxygens, providing favorable conditions for the dynamic participation of lattice oxygens in the n-propanol oxidation process. Figure 3 (gh), high-resolution Ni 2p spectroscopy shows that Ni in the sample is mainly in the form of 2... + It exists in the form of Ni 2p 3 / 2 and Ni 2p 1 / 2 The binding energies are located at 855.68 eV and 873.33 eV, respectively, accompanied by satellite peaks centered at binding energies of 861.82 eV and 880.28 eV. High-resolution V 2p spectra show two peaks centered at binding energies of 516.98 eV and 524.25 eV, corresponding to V 2p... 3 / 2and V 2p 1 / 2 Further peak analysis results indicate that species V coexists in multiple valence states, including V... 3+ V 4+ V 5+ Three valence states, among which V 4+ The composition is dominant. Comparing MXene / TiO2 / NiO and V-NiO, the Ni 2p and V 2p peaks of MXene / TiO2 / V-NiO show a positive shift, indicating a decrease in electron density around the Ni and V sites. Simultaneously, the Ti 2p peak shifts towards lower binding energies, indicating that Ti-related species gain electrons and exhibit electron enrichment characteristics. These phenomena suggest a significant charge redistribution at the MXene / TiO2 / V-NiO interface, with electrons tending to transfer from V-NiO to MXene / TiO2, thus forming strong interfacial electronic interactions.

[0061] Example 6 The materials prepared in Example 3 and Comparative Examples 1-4 were used for n-propanol gas detection performance testing, as detailed below: Five test points were selected within a temperature range of 200 ℃ to 400 ℃, and the test was repeated several times at each temperature test point. Figure 4 (ab) MXene and MXene / TiO2 exhibited low response values ​​with minimal fluctuations as the operating temperature increased. V-NiO showed a certain response value, but the response value of MXene / TiO2 / V-NiO gradually increased between 200-300 °C, reaching a peak response of approximately 68 at 350 °C. This result reflects that the construction of the MXene / TiO2 heterostructure effectively enhances the response capability of V-NiO to n-propanol gas. Comparing MXene / TiO2 / NiO and MXene / TiO2 / V-NiO, both reached peak responses at 350 °C, but with V doping, the peak response of MXene / TiO2 / V-NiO was approximately three times that of the former. As the temperature continued to rise, the response values ​​of both materials gradually decreased, exhibiting typical volcano-type sensor characteristics. Therefore, all subsequent tests were conducted at the optimal operating temperature of 350 °C. The experimental results indicate that an appropriate amount of MXene / TiO2 can effectively improve the performance of V-NiO. Therefore, by constructing a heterostructure, the gas-sensing performance of n-propanol was significantly improved, and 350 °C was selected as the optimal operating temperature in the subsequent gas-sensing tests.

[0062] The dynamic responses of different samples to n-propanol were recorded in continuous and repeated tests under an atmosphere of 100 ppm n-propanol. Figure 4(cg)). Each sample was tested repeatedly for 12 cycles under the same conditions. In any cycle, the introduction of n-propanol gas was observed to immediately cause a change in the material's resistance, which then tended to stabilize at a certain value. With the release of n-propanol and the introduction of air, the resistance value eventually returned to its original value. After repeated testing over multiple cycles, the data showed high stability. The construction of the heterostructure has a significant impact on the response to n-propanol gas. Compared with MXene / TiO2 / NiO ( Figure 4 (d)), V-NiO ( Figure 4 (e) MXene / TiO2 ( Figure 4 (f) and MXene ( Figure 4 Compared to the response value of (g), MXene / TiO2 / V-NiO ( Figure 4 (c) The average response value increased significantly. Figure 4 (h) is a one-cycle image of the response and recovery curves of MXene / TiO2 / V-NiO to n-propanol gas. Response time refers to the time required for the sensor to reach 90% of its maximum resistance when exposed to the gas, while recovery time refers to the time required for the sensor to recover to 90% of its initial resistance after exposure to air. The test results show that the response and recovery times of this sample are approximately 31 s and 89 s, respectively. Therefore, selectivity is another key parameter for evaluating gas sensors. Figure 4 (i) Under the same test conditions, MXene / TiO2 / V-NiO was placed in a common ambient gas atmosphere of 100 ppm (gases including n-propanol, acetic acid, methanol, ethanol, ammonia, acetone, formaldehyde, benzene, toluene, hydrogen sulfide, diethyl ether, and ethyl acetate). The results showed that MXene / TiO2 / V-NiO exhibited significant selectivity for n-propanol gas in response values ​​under various gas atmospheres.

[0063] The dynamic sensing performance of each sensor was tested under different concentrations of n-propanol. Figure 5 (ae)). The study found that MXene / TiO2 / V-NiO still showed a response to 1 ppm n-propanol. The response value also showed a significant upward trend with increasing n-propanol gas concentration. As the n-propanol concentration increased, the response value of MXene / TiO2 / V-NiO also continuously increased, and its response value remained superior to MXene / TiO2 / NiO and V-NiO, indicating that it has a wide detection range and potential quantitative detection capability. MXene / TiO2 and MXene showed almost no response across the entire concentration range. Figure 5(f) demonstrates the linear fit of MXene / TiO2 / V-NiO for different concentrations (from 1 ppm to 2000 ppm) of n-propanol gas at 350 °C. According to the formula LOD = κσ / S (where κ is typically set to 3, σ represents the standard deviation of the measurement, and S represents the slope), the limit of detection (LOD) is approximately 127.6 ppb, far below the occupational exposure limit and hazardous concentration level of n-propanol. This result indicates that the MXene / TiO2 / V-NiO sensor has potential application value in early warning of n-propanol leaks, environmental monitoring, and occupational safety protection.

[0064] like Figure 6 (a) shows the changes in the response value and baseline resistance of MXene / TiO2 / V-NiO over a 4-month period. The sensor's response value and baseline remained relatively stable over the 4-month period, demonstrating the sample's good stability. This surface... Figure 6 (b) It shows that when the relative humidity is 20% to 80%, the sensor response value only decreases slightly as the relative humidity increases, indicating that the MXene / TiO2 / V-NiO composite structure can maintain effective gas adsorption, reaction process and charge transport behavior in humid environments, demonstrating good moisture resistance.

[0065] Example 7 To further elucidate the band structure arrangement of V-NiO prepared in Comparative Example 3 and MXene / TiO2 prepared in Comparative Example 2 in the formed heterostructure, a series of characterizations were performed (including UPS, ultraviolet surface-visible light absorption spectroscopy and Mott-Schottky test).

[0066] The result is as follows Figure 7 As shown, Figure 7 (a) and Figure 7 The test data for the UPS in (d) yields the work functions of V-NiO and MXene / TiO2, which are 6.65 eV and 7.01 eV, respectively. Based on the results of the violet-visible absorption spectroscopy, the band gaps of V-NiO and MXene / TiO2 are 2.67 eV and 2.01 eV, respectively. Figure 7 (b) and 3.47 eV ( Figure 7 (e)). According to Mott-Schottky tests, the conduction band of V-NiO is approximately -0.24 V ( Figure 7 (c)), while the valence band of MXene / TiO2 is approximately 0.29 V ( Figure 7 (f)).

[0067] Example 8 To investigate the real-time gas-sensing behavior of n-propanol on the surface of the MXene-based TiO2 / V-doped NiO multi-interface heterojunction prepared in Example 3, in-situ Fourier transform red surface spectroscopy (FTIR) was performed.

[0068] The result is as follows Figure 8 As shown in (a), the red surface spectrum records the changes over a period of 0 to 60 minutes. Figure 8 As shown in (b), 3620-3700 cm -1 The absorption band at this location can be attributed to isolated hydroxyl groups on the material surface. As the reaction proceeds, the signal in this region gradually weakens, indicating that the isolated hydroxyl sites on the material surface are gradually occupied during the n-propanol adsorption process and participate in the interfacial adsorption and initial activation of n-propanol molecules. Meanwhile, at 3080-3210 cm⁻¹... -1 The broadened absorption band in this region gradually intensifies, and the signal in this region can be attributed to the OH stretching vibration, possibly originating from the combined effects of adsorbed n-propanol and hydroxyl-related species such as adsorbed water molecules generated during the reaction. This phenomenon indicates that n-propanol molecules can interact with hydroxyl groups and reactive oxygen sites on the MXene / TiO2 / V-NiO surface, thereby promoting its initial adsorption and activation. This surface shows a significant increase in absorption bands in the 2930-2980 cm⁻¹ region. -1 The absorption peaks within the material can be attributed to the CH stretching vibrations (-CH3, -CH2-) of the adsorbed n-propanol or n-propoxy transition. The absorption peaks gradually increase and tend to stabilize, indicating that the amount of n-propanol molecules adsorbed on the material surface gradually increases over time and tends to reach equilibrium after continuous exposure. Figure 8 (c) Displayed in the wavenumber range of 1520–1620 cm⁻¹ -1 and 1720-1750 cm -1 The absorption peaks in the region are synchronously enhanced, particularly in the 1720-1750 cm⁻¹ range. -1 The nearby absorption peaks can be attributed to the carbonyl C=O stretching vibration, indicating that the adsorbed n-propanol undergoes an oxidation reaction on the material surface, forming oxidation products such as aldehydes or carboxylic acids. Meanwhile, the 1520-1620 cm⁻¹... -1 The enhanced absorption signal in the region can be attributed to the combined contribution of the HOH bending vibrations of adsorbed water molecules and the vibrations of surface carboxylate transition bodies. This is particularly evident in the 2340–2380 cm⁻¹ region. -1 Absorption peaks within the region ( Figure 8(d) The peak gradually increases with the duration of n-propanol exposure, which can be attributed to the stretching vibration of CO2 molecules. This enhancement of the absorption signal indicates further deep oxidation of the surface oxidized transition body. These results suggest that n-propanol exhibits a continuous oxidation pathway on the MXene / TiO2 / V-NiO surface: n-propanol is first adsorbed onto hydroxyl groups, reactive oxygen species, and heterojunction active sites on the MXene / TiO2 / V-NiO surface, forming the n-propoxy transition body with the combined participation of surface reactive oxygen species and lattice oxygen. This transition body is further oxidized to carbonyl transition bodies such as aldehydes and carboxylic acids, and finally undergoes deep oxidation to generate CO2 and H2O.

[0069] The above description is only a preferred embodiment of the present invention, but the scope of protection of the present invention is not limited thereto. Any equivalent substitutions or modifications made by those skilled in the art within the scope of the technology disclosed in the present invention, based on the technical solution and inventive concept of the present invention, should be covered within the scope of protection of the present invention.

Claims

1. An MXene-based TiO2 / V-doped NiO multi-interface heterojunction, characterized in that, The MXene-based TiO2 / V-doped NiO multi-interface heterojunction includes a substrate and a transition layer and a surface layer sequentially disposed on the substrate; Wherein, the substrate is a two-dimensional MXene nanosheet, the transition layer is TiO2 nanoparticles, and the surface layer is V-doped NiO nanosheet; A metal-semiconductor interface is formed between the two-dimensional MXene nanosheets and the TiO2 nanoparticles; a semiconductor heterostructure interface is formed between the TiO2 nanoparticles and the V-doped NiO nanosheets.

2. The MXene-based TiO2 / V-doped NiO multi-interface heterojunction according to claim 1, characterized in that, In the MXene-based TiO2 / V-doped NiO multi-interface heterojunction, the loading of V-doped NiO nanosheets is 70-85 wt%, and the V doping amount is 4-7 wt%.

3. The MXene-based TiO2 / V-doped NiO multi-interface heterojunction according to claim 1, characterized in that, The specific surface area of ​​the MXene-based TiO2 / V-doped NiO multi-interface heterojunction is 80 m². 2 / g~100 m 2 / g; The MXene nanosheets have a lateral dimension of 4 μm to 11 μm, the TiO2 nanoparticles have a size of 4 nm to 10 nm, and the V-doped NiO nanosheets have a thickness of 30 nm to 60 nm.

4. The method for preparing an MXene-based TiO2 / V-doped NiO multi-interface heterojunction according to any one of claims 1 to 3, characterized in that, Includes the following steps: S1. Preparation of two-dimensional MXene nanosheets; S2. Ni-V double hydroxide nanosheets are grown in situ on the surface of the two-dimensional MXene nanosheets by water bath method to obtain the transition product MXene / Ni-V LDH heterojunction. S3. The transition product MXene / Ni-V LDH heterojunction is calcined to oxidize the MXene portion in situ to generate TiO2 nanoparticles, and the Ni-V double hydroxide is converted into V-doped NiO nanosheets to obtain the MXene-based TiO2 / V-doped NiO multi-interface heterojunction.

5. The preparation method according to claim 4, characterized in that, In S1, the specific preparation method of the two-dimensional MXene nanosheets includes the following steps: Lithium fluoride was dissolved in concentrated hydrochloric acid and stirred to obtain a reaction solution; Aluminum carbide was added to the reaction solution for a water bath reaction. After the reaction, the solution was washed with dilute hydrochloric acid and deionized water in sequence, and then centrifuged. The solution was then subjected to ultrasonic exfoliation and reaction under an inert gas atmosphere. After the reaction, the solution was centrifuged, the supernatant was taken, frozen, and dried to obtain the two-dimensional MXene nanosheets.

6. The preparation method according to claim 5, characterized in that, The molar ratio of lithium fluoride to aluminum carbide is 3.5~15:1; The concentration of the concentrated hydrochloric acid is 10 mol / L to 12 mol / L, and the concentration of the dilute hydrochloric acid is 0.5 mol / L to 1.5 mol / L. The ultrasonic power during ultrasonic ablation is 50 W to 70 W.

7. The preparation method according to claim 4, characterized in that, In S2, the specific preparation method of the transition product MXene / Ni-V LDH heterojunction includes the following steps: Ni(NO3)2·6H2O, VCl3, and CO(NH2)2 were dissolved in deionized water and stirred. During the stirring process, the two-dimensional MXene nanosheets were added to obtain the reaction solution. The reaction solution was placed in a reaction vessel and then heated to carry out the reaction at a temperature of 100-120 °C for 10-12 h. After the reaction was completed, the mixture was washed and dried to obtain the transition product MXene / Ni-V LDH heterojunction. The molar ratio of Ni(NO3)2·6H2O, VCl3, and CO(NH2)2 is 13~14:0.8~3:0.0055~0.0065.

8. The preparation method according to claim 4, characterized in that, In S3, the specific preparation method of the MXene-based TiO2 / V-doped NiO multi-interface heterojunction includes the following steps: The transition product MXene / Ni-V LDH heterojunction was placed in a container and spread out evenly. The container was placed in a muffle furnace for high-temperature calcination at a reaction temperature of 300~350 ℃ for 1~3 h to obtain the MXene-based TiO2 / V-doped NiO multi-interface heterojunction.

9. A gas sensor, characterized in that, The MXene-based TiO2 / V-doped NiO multi-interface heterojunction described in any one of claims 1 to 3 is used as a gas-sensitive material.

10. The application of the gas sensor according to claim 9 in detecting the volatile organic compound n-propanol gas.